(untitled) (Gestión y Gerencia, 2019)
This essay tries to show how certain governmental dispositions, adopted between 2007 and 2015, prevent companies located in Venezuela from rationally use their plants and equipment, according to the generally accepted conventional canons. The restrictive measures of business freedom to incorporate or withdraw workers from the payroll when the variations in the demand for their products advise it or when the input provision is not enough, condemns companies, public or private to operate in a decreasing marginal returns phase. This damages their productivity, increases costs and powers inflation. This conclusion is reached starting from the Theory of Production and Costs, in an environment in which prices are set by the political authority